Efficacy of (+)-Lariciresinol to Control Bacterial Growth of Staphylococcus aureus and Escherichia coli O157:H7 - Bajpai, Vivek K.; Shukla, Shruti; Paek, Woon K.; Lim, Jeongheui; Kumar, Pradeep; Kumar, Pankaj; Na, MinKyun (Frontiers in Microbiology, 2017)
This study was undertaken to assess the antibacterial potential of a polyphenolic compound (+)-lariciresinol isolated from Rubia philippinensis against selected foodborne pathogens Staphylococcus aureus KCTC1621 and Escherichia coli O157:H7. (+)-lariciresinol at the tested concentrations (250 µg/disc) evoked a significant antibacterial effect as a diameter of inhibition zones (12.1-14.9 mm) with minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) values of 125-250 and 125-250 µg/mL, respectively. Furthermore, (+)-lariciresinol at MIC showed reduction in bacterial cell viabilities, efflux of potassium (K+) ions and release of 260 nm materials against E. coli O157:H7 and S. aureus KCTC1621. Moreover, deteriorated cell wall morphology of E. coli O157:H7 and S. aureus KCTC1621 cells treated with (+)-lariciresinol at MIC further confirmed its inhibitory effect against the tested pathogens, suggesting it to be an alternative means of antimicrobials.